Effect of self-seismic oscillations of the foundation on the readout of a ballistic gravimeter with an induction-dynamic catapult - Bolyukh, V. F.; Omel’chenko, A. V.; Vinnichenko, A. I. (Springer Science+Business Media New York, 2015)
A mathematical model is developed for the vertical oscillations produced in the base–foundation system of a laser ballistic gravimeter with an induction-dynamic catapult and a symmetric configuration for measuring the acceleration of gravity. Analytic expressions are obtained for the force pulse acting on the foundation during acceleration of the test body that describe the oscillations in the mechanical system of the ballistic laser gravimeter. The effects of the measurement duration and the damping coefficient of the foundation on the results of measurements of the acceleration of gravity are studied.
Keywords: force pulse; transfer function; foundation vibrations; ballistic laser gravimeter; base stiffness coefficient; damping coefficient